A new boreopterid pterosaur from the Lower Cretaceous of western Liaoning, China, with a reassessment of the phylogenetic relationships of the Boreopteridae. (July 2014) - Jiang, Shun-Xing; Wang, Xiao-Lin; Meng, Xi; Cheng, Xin
Abstract : A new species of boreopterid pterosaur from the new fossil locality, Heichengzi, Beipiao, western Liaoning, China allows a reassessment of the Boreopteridae. In this new analysis, three species, Boreopterus cuiae, Boreopterus giganticus n. sp., and Zhenyuanopterus longirostris, are included within the Boreopteridae united by the autopomorphic occurrence of two main tooth morphologies, an equal length of the tibia and femur, and weak feet. Other taxa previously placed within the Boreopteridae are not in a monophyletic group with the former three species. Boreopterus has fewer teeth and a shorter tooth row than that in Zhenyuanopterus . This new Boreopterus species has a large size, a piriform orbit, an extensively fenestrated lacrimal, and a posteriorly directed lacrimal process, that differs from Boreopterus cuiae .